2009
DOI: 10.1007/s10067-009-1095-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rituximab treatment on endothelial dysfunction, carotid atherosclerosis, and lipid profile in rheumatoid arthritis

Abstract: Increased cardiovascular mortality has been associated with rheumatoid arthritis (RA). There have been reports indicating that tumor necrosis factor blockers may exert favorable but transient effects on lipid profile, flow-mediated vasodilation (FMD) of the brachial artery, and common carotid intima-media thickness (ccIMT) in RA. In this study, we assessed the effects of rituximab on FMD, ccIMT, and lipid profile. Five female RA patients received two infusions of 1000 mg rituximab i.v. High-resolution B-mode u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 14 publications
3
103
1
8
Order By: Relevance
“…Lowering of plasma total cholesterol, raised HDL levels, and decreased intima-media thickness in the common carotid artery were also observed in the trial. 137 Although rare, anti-CD20 therapy has shown adverse effects in the form of CV events, causing patients to be withdrawn from anti-CD20 clinical trials. 138 Nevertheless, with regard to the concern over the use of anti-CD20 therapy for CVD, there is debate on whether statins decrease the efficacy of anti-CD20 agents.…”
Section: Targeting Effector T Cell Responsesmentioning
confidence: 99%
“…Lowering of plasma total cholesterol, raised HDL levels, and decreased intima-media thickness in the common carotid artery were also observed in the trial. 137 Although rare, anti-CD20 therapy has shown adverse effects in the form of CV events, causing patients to be withdrawn from anti-CD20 clinical trials. 138 Nevertheless, with regard to the concern over the use of anti-CD20 therapy for CVD, there is debate on whether statins decrease the efficacy of anti-CD20 agents.…”
Section: Targeting Effector T Cell Responsesmentioning
confidence: 99%
“…In a study involving 49 RA patients, the atherogenic index significantly improved (~9%) after 6 months treatment with rituximab, indicating the beneficial effects on lipid profile along with improvement of disease activity [98]. Study involving small number of RA patients have also demonstrated that rituximab improves carotid atherosclerosis and endothelial function (Table 1) [99]. These data suggest the potential benefit of novel biologics in preventing CVD in RA patients.…”
Section: Biologics Therapy and Atherosclerosismentioning
confidence: 93%
“…При-менение традиционных базисных противовоспалительных препаратов (БПВП), в частности метотрексата (МТ), а так-же генно-инженерных биологических препаратов (ГИБП), таких как ингибиторы фактора некроза опухоли α (ФНОα), связано со значительным снижением риска ССЗ у пациен-тов с РА [35,38,40,[42][43][44][45]. В пилотных исследованиях по-казано, что снижение активности РА коррелирует с сурро-гатными маркерами риска развития ССЗ: уменьшением толщины комплекса интима-медиа на фоне терапии тоци-лизумабом или ритуксимабом (РТМ) [46][47][48]; улучшением артериальной ригидности и жесткости аорты на фоне лече-ния МТ и ингибиторами ФНОα [49][50][51][52].…”
Section: рекомендация 1 для снижения риска ссз необходим эффективныйunclassified
“…Применение ингибиторов ФНОα и БПВП (в основном MT) ассоциируется с увеличением концентрации ОХС, ХС ЛПНП и, в большей степени, ХС ЛПВП, что улучшает от-ношение ОХС/ХС ЛПВП [57][58][59][60][61][62][63][64][65]. В исследованиях сооб-щалось о положительном эффекте РТМ, тоцилизумаба и тофацитиниба на показатели липидного спектра крови [47,[66][67][68][69][70][71][72]. Однако общий эффект лечения этими препа-ратами проявляется в увеличении уровней липидов крови без изменений отношения ОХС/ХС ЛПВП [57,[68][69][70][71][72].…”
Section: рекомендация 4 общий хс (охс) и хс липопротеидов высокой плunclassified